Isolation and characterization of the highly repeated fraction of the banana genome - Hribová, E; Dolezelová, M; Town, C D; Macas, J; Dolezel, J (Cytogenetic and genome research, 2007)
Although the nuclear genome of banana (Musa spp.) is relatively small (1C approximately 610 Mbp for M. acuminata), the results obtained from other sequenced genomes suggest that more than half of the banana genome may be composed of repetitive and non-coding DNA sequences. Knowledge of repetitive DNA can facilitate mapping of important traits, phylogenetic studies, BAC-based physical mapping, and genome sequencing/annotation. However, only a few repetitive DNA sequences have been characterized in banana. In this work, we used DNA reassociation kinetics to isolate the highly repeated fraction of the banana genome (M. acuminata 'Calcutta 4'). Two libraries, one prepared from Cot </=0.05 DNA (2,688 clones) and one from Cot </=0.1 sequences (4,608 clones), were constructed, and 614 DNA clones were chosen randomly for sequencing and further characterization. Dot-plot analysis revealed that 14% of the sequenced clones contained various semi-tandem and palindromic repeated sequences. 'BLAST' homology searches showed that, in addition to tandem repeats, the Cot libraries were composed mainly of different types of retrotransposons, the most frequent being the Ty3/gypsy type monkey retrotransposon. Selected sequences displaying tandem organization properties were mapped by PRimed IN Situ DNA labeling (PRINS) to the secondary constriction on metaphase chromosomes of M. acuminata 'Calcutta 4'. Southern hybridization with selected BAC clones carrying 45S rDNA confirmed the presence of the tandem repeats in the 45S rDNA unit. This work significantly expands the knowledge of the repetitive fraction of the Musa genome and organization of its chromosomes.
Keywords: banánovník; tandemové repetitivní sekvence; DNA, Plant; sekvence nukleotidů; buněčné klony; DNA, Ribosomal; repetitivní sekvence nukleových kyselin; Musa; sekvenční homologie nukleových kyselin; Tandem Repeat Sequences; genová dávka; Genome, Plant; Repetitive Sequences, Nucleic Acid; Clone Cells; in situ značení DNA s primerem; Base Sequence; Sequence Homology, Nucleic Acid; DNA rostlinná; ribozomální DNA; Chromosomes, Artificial, Bacterial; genom rostlinný; Primed In Situ Labeling; umělé bakteriální chromozomy; Gene Dosage; genová knihovna; Gene Library